The Urgensi Perlindungan Jurnalis dalam Konteks Konflik Bersenjata Israel-Palestina Pasca 7 Oktober 2023 - Paramitha, Devy Indah; Dduha, Syamsi; Al Farauqi, Mohamad Dziqie Aulia; Damarin Tyas, Intan Kinanti (Indonesia Center for Middle East Studies, 2024)
Based on the Geneva Convention, journalists are included in the special protection group during armed conflict. However, it is not uncommon for journalists to become victims during war. This study aims to explain the urgency of protection for journalists in armed conflict by taking a case study of the Israeli-Palestinian conflict after October 7, 2023. The research method used is qualitative descriptive analytical with the approach of the special protection concept of the Geneva Convention. The results of the study show that the large number of journalist victims in the Israeli-Palestinian conflict after October 7, 2023, is evidence that the rules for protection for war journalists have been inconsistent while the risks for journalists in the conflict zone continue to increase. Universal recognition of the application of journalist protection laws is increasingly urgent to protect journalists during armed conflict. The role of International Organizations is critical in voicing the urgency of protecting journalists while on duty.